Whole Genome Sequence of Alternaria alternata, the Causal Agent of Black Spot of Kiwifruit - Huang, Ke; Tang, Jianming; Zou, Yong; Sun, Xiangcheng; Lan, Jianbin; Wang, Wei; Xu, Panpan; Wu, Xiangwei; Ma, Rui; Wang, Qi; Wang, Zhenshuo; Liu, Jia (Frontiers in Microbiology, 2021)
Alternaria alternata is a pathogen in a wide range of agriculture crops, and causes significant economic losses. A strain of A. alternata (Y784-BC03) was isolated and identified from ‘Hongyang’ kiwifruit and demonstrated to cause black spot infections on fruits. The genome sequence of Y784-BC03 was obtained using Nanopore MinION technology. The assembled genome is composed of 33,869,130 bp (32.30 Mb) comprising 10 chromosomes, and 11954 genes. A total of 2180 virulence factors were predicted to be present in the obtained genome sequence. The virulence factors comprised genes encoding secondary metabolites, including host-specific and non-host-specific toxins, cell wall-degrading enzymes, and major transcriptional regulators. The predicted gene clusters encoding genes for the biosynthesis and export of secondary metabolites in the genome of Y784-BC03 were associated with host-specific toxins, including ACR-toxin, and non-host-specific toxins, including cercosporin , dothistromin and versicolorin B. Major transcriptional regulators of different mycotoxin biosynthesis pathways were identified, including the transcriptional regulators, polyketide synthase, P450 monooxygenase, and major facilitator superfamily transporters.